Mitochondrial evidence on the phylogenetic position of the Southeast Asian catfish genus Encheloclarias Myers, 1937 (Actinopterygii: Siluriformes: Clariidae): Evolutionary and conservation implications - Lavoue, Sebastien (Pensoft Publishers, 2024)
The phylogenetic position of the Southeast Asian catfish genus Encheloclarias Myers, 1937 within the family Clariidae is inferred herein using three mitochondrial nucleotide markers: cytochrome b, cytochrome oxidase subunit I, and 16S rRNA genes. We found that Encheloclarias is neither exclusively related to the African taxa having extended neural spines posterior to the dorsal fin (Encheloclarias shares with some of these taxa the presence of an adipose fin, as opposed to absent in all other clariid taxa) nor to the Asian species of the genus Clarias Scopoli, 1777. Encheloclarias is hypothesized to be the sister group of all other clariids, except Horaglanis Menon, 1951. The inferred position of Encheloclarias confirms that the adipose fin in this genus has an evolutionary origin independent to that of the adipose fin found in some African clariids. Encheloclarias is not only ecologically remarkable, being adapted to acidic peat swamps in Southeast Asia, but it is also an ancient lineage sheltering in these habitats. However, the precise timing of the colonization of peat swamps by Encheloclarias remains to be investigated. The phylogenetic position of Encheloclarias further underscores the importance of studying and protecting the remaining peat swamp habitats in Southeast Asia and their distinctive aquatic fauna.